أثر المتغيرات الاجتماعية للأسرة على إنفاق طلبة جامعة تشرين - أحمد, طالب; درويش, رامي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The aim of this study was to study the impact of social variables on the expenditure of Tishreen university students. Three indicators were identified to measure the social variables of the family, including the cultural and professional status of the family, size of the family and family stability. A questionnaire was distributed to a sample of 450 students from Tishreen University. 420 questionnaires were retrieved, 409 were valid for the study. The study results indicate that the cultural and professional status of the family, the size of the family, and the family stability have a significant effect on expenditure of the Tishreen university students in Lattakia Governorate. هدفت هذه الدراسة إلى دراسة أثر المتغيرات الاجتماعية للأسرة على إنفاق طلبة جامعة تشرين، تم تحديد ثلاثة مؤشرات يتم من خلالها قياس المتغيرات الاجتماعية للأسرة تشمل كل من المكانة الثقافية والمهنية للأسرة، حجم الأسرة، الاستقرار الأسري. تم توزيع استبانه على عينة بلغت 450 طالب من طلاب جامعة تشرين وقد تم استرداد 420 استبيان منها 409 استبيان صالح للدراسة،وتم التوصل إلى أن هناك تأثير ذو دلالة إحصائية للمكانة الثقافية والمهنية للأسرة، ولحجم الأسرة، وللاستقرار الأسري على إنفاق طلبة جامعة تشرين في محافظة اللاذقية.